2019
DOI: 10.1096/fj.201800390rr
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatidic acid generated by PLD2 promotes the plasma membrane recruitment of IQGAP1 and neointima formation

Abstract: Very little is known about how lipid signaling regulates intima hyperplasia after vascular injury. Herein, we report that deletion and pharmacological inhibition of phospholipase D (PLD)2, which generates the signaling lipid phosphatidic acid (PA), reduced neointimal formation in the mouse carotid artery ligation model. PLD2 deficiency inhibits migration of vascular smooth muscle cells (VSMCs) into the intima in mice as well as migration and formation of membrane ruffles in primary VSMCs. PA specifically binds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…Similarly, we obtained the same results using the in vitro chemical inhibition of PLD2 in HUVECs. PLD2 is a lipid signal transduction enzyme whose classical function is to catalyze the hydrolysis of PC to generate the signal molecule PA [39]. We next tested whether the PA increase was positively related to STAT3 phosphorylation, con rming this hypothesis.…”
Section: Discussionmentioning
confidence: 93%
“…Similarly, we obtained the same results using the in vitro chemical inhibition of PLD2 in HUVECs. PLD2 is a lipid signal transduction enzyme whose classical function is to catalyze the hydrolysis of PC to generate the signal molecule PA [39]. We next tested whether the PA increase was positively related to STAT3 phosphorylation, con rming this hypothesis.…”
Section: Discussionmentioning
confidence: 93%
“…50 Moreover, in symptomatic plaques, enhanced FFAR2-FAM3C and PLD2-ARF1 interactions favored EREG + monocytes to promote monocyte adhesion, macrophage phagocytosis, EC hyperpermeability, and SMC migration. 51,52 Of course, there were still many crucial ligand-receptor pairs in B cell, DC, neutrophil, NK cell, EC, and SMC subtypes that might be responsible for cerebrovascular events and deserved further exploration (Figures S12 and S13). In conclusion, the heterogeneity within carotid atherosclerosis was comprehensively dissected, with plaque-specific or cerebrovascular event–promoting cell subtypes identified, core genes and cellular mechanisms explored, and an unprecedented ultra-high-precision cellular landscape of the atherosclerotic microenvironment depicted (Figure 7E).…”
Section: Resultsmentioning
confidence: 99%
“…PLD activation in cells results in generation of PA, which is recognized as a key lipid secondmessenger involved in a number of cellular responses such as proliferation (29,30), vesicular trafficking (31,32), cytoskeletal reorganization (33)(34)(35), , activation of NADPH oxidase (36), secretion of pro-inflammatory cytokines (55), neo-intima formation (56), and endothelial barrier function [58]. Studies describing the role of PLD in regulating endothelial permeability were carried out in vitro using either bovine pulmonary artery (57) or human umbilical vein ECs (58).…”
Section: Discussionmentioning
confidence: 99%
“…Tyrosine phosphorylation of VEcadherin at 658 by c-Src, facilitates VE-cadherin internalization in a β-arrestin dependent manner (3), and the internalized VE-cadherin enters endosomal compartments and is either recycled to the plasma membrane or subjected to degradation (68). Recent studies have shown that spatiotemporally generated PA from PLD2 acts as signaling platforms for MT1-MMP surface trafficking and lung metastasis of breast cancer cells (69), ERK signaling in cancer cells (47), podosome formation (70), and recruitment of IQGAP1 associated with neo-intima formation (56). In addition to PLD2, PLD1 mediated PA generation in microdomains promotes vesicular fusion to the plasma membrane during exocytosis of large dense-core granules [70]; however, a role for PA confinement in microdomains in VE-cadherin redistribution to AJs is unknown.…”
Section: Discussionmentioning
confidence: 99%